‘It’s like the Hatfields & McCoys’ : recreational angler perspectives on intra-fisheries conflict in insular Newfoundland - Murray, Colin Ian, 1985- (2019)
Verkefnið er lokað til 30.06.2020. Recreational angling is a pastime that captures a huge following globally. Because of the enormous participation rate in the leisure activity, angling can have negative environmental impacts. However, the activity is also hugely important due to economic, and environmental and human health benefits. A feedback loop develops when the participants demonstrate a high level of care towards the resource, contributing considerable funds, time, and effort to protecting the target species through habitat restoration and environmental lobbying. This creates a system where a strong fishery promotes a high level of care and vice-versa. These benefits transcend the target species or the recreational activity, promoting economic, cultural, and environmental sustainability. The Canadian province of Newfoundland and Labrador has the highest angler participation rate in the country, and Atlantic salmon (Salmo salar) is arguably the most prized target. However, there is considerable tension between angler sub-groups. Live-release angling has risen in popularity but has not been universally adopted or accepted in Newfoundland and Labrador as a management measure and has further been criticised as a voluntary restraint. The tension between live-release and retention anglers threatens to undermine the feedback loop which offsets and mitigates negative and promotes positive impacts. Tension can be exacerbated by a lack of cooperation between the federal and provincial management, and a lack of agency trust. Managers must look outside recreational fisheries management to manage Atlantic salmon. For the recreational fishery to continue providing economic, social and environmental benefits, sacrifices must be made exterior to the fishery itself, as in-fishery solutions regarding further restrictive regulation are increasingly being viewed as insincere, and unproductive attempts to curb a declining population.